Information Propagation and Bionic Evolution Control of the SEBAR Model in a Swarm System - Yankai Shen; Xinan Liu; Hong Du; Xiao Ma; Long Xin (Applied Sciences, 2025)
To explore the coupling relationship between information propagation behaviors and evolution dynamics in swarm systems, this paper establishes the SEBAR model based on mean field theory with a macroscopic view of information dissemination. Then, the balance points and basic reproduction number are calculated and a proof of equilibrium stability from the point of view of system stability is given. In addition, the influence of model parameters on propagation behaviors is also analyzed. To stimulate the emergence of cooperative behaviors in a swarm system, a repeated “prisoner’s dilemma” game based on controllable individuals is proposed under the framework of bionic “soft control”. The combination of information propagation and game strategies is used to realize information regulation. The simulation results show that the proposed models and methods can reflect the information communication patterns and evolution characteristics. It also illustrates the viability and effectiveness of regulating information through the evolutionary game.